Validation of the unique OUES scale (Î”V02, VE slope) in functional reserve assessment of cardiorespiratory system for Iranian children - Akbar Sazvar; Farzad Nazem (Türk Spor ve Egzersiz Dergisi)
The aim of this study was, validation of OUES against the traditional index of VO2max for Iranian children is inevitable. The increasing application of Graded exercise test (GXT) to determine the clinical symptoms or achieve a safe level of physical and metabolic responses in a wide range of healthy or patients individuals is common .On the other hand, the findings a reliable physiologic indicator that can evaluate the practical storage level of cardiorespiratory without the need to perform tests above the lactate threshold is important. 72 healthy young males with a mean age 13.95 ± 1.84(years) and body mass index of 19.91 ± 3.4(kg /m2) participated in an aerobic exhaustive test and VO2max value using gas analyzer method        (VE, VO2, VCO2 values) were measured with a breath by breath style. Then pattern of the predictor line between OUES and VO2max indexes was determined. Results showed that, OUES index has a high validity for evaluating the performance of children's cardiorespiratory functional reserve (R2 = 0.90, SEE=292.2). A Significant relationship between the QUES amp;VO2max indices at different times of GXT during maximal aerobic test was obtained (R = 0.81- 0.95, p lt;. 001). In studies of screening and clinical diagnosis of cardiovascular system performance, the supplying of OUES index during the ergometry tests in the lower than lactate threshold conditions is usable for Iranian healthy boys. Application of this sensitive index to compare the performance of the cardiorespiratory system of healthy children with counterpart patients can be also significant in submaximal exercise rather than the exhaustive training protocols.